Chemical characterization and antimicrobial activity of the essential oil of the leaves of Libanothamnus neriifolius (Asteraceae) - Aparicio-Zambrano, Rosa (2019)
The essential oil of the fresh leaves of Libanothamnus neriifolius (B. ex H) Ernst. was obtained by the hydrodistillation method using the Clevenger trap, obtaining 1.8 mL (0.087% yield). The essential oil was characterized by the method of gas chromatography coupled to mass spectrometry (GC/MS), identifying as main compounds, that β-phelandrene (29.0%), α-phelandrene (19.9%), α-pinene (13.6%), and α-tujene (12.4%) were the most abundant constituents. Antimicrobial activity of the oil was tested Staphylococcus aureus ATCC25923, Enterococcus faecalis ATCC 29212, Escherichia coli ATCC 25922, Klebsiella pneumoniae ATCC 23357, Pseudomonas aureginosa ATCC 27853, Candida albicans CDC-B385, Candida krusei ATCC 6258 by the agar difusion method. It showed activity against S. aureus with MIC of 50 μL/mL. With respect to antifungic activity it was active against C. albicans and C. krusei with MIC of 700 μL/mL and 500 μL/mL respectively. This is the first report on the antimicrobial activity of this L. neriifolius and for the genere Libanothamnus.